ASPEK HUKUM PENINJAUAN KEMBALI LEBIH DARI SATU KALI DALAM PERKARA PIDANA (PERSPEKTIF PENEGAKAN KEADILAN, KEPASTIAN DAN KEMANFAATAN HUKUM) - Suhariyanto, Budi (Jurnal Hukum dan Peradilan, 2015)
Constitutional Court Decision No. 34 / PUU-XI / 2013 has opened the space PK is not just one time as provided for by the Article 268 paragraph (3) Criminal Procedure Code so that PK can be done many times during found and submission of PK Novum although it has done previously. Perspective is the basis of this decision is justice. Responding to the verdict of the Constitutional Court, the Supreme Court publishes SEMA No. 7 Year 2014 on Reconsideration Request Submission In Criminal Case. Through the SEMA Supreme Court warned that provisions PK only once outside the Article 268 Criminal Procedure Code which was canceled by the Constitutional Court, therefore, PK criminal cases (in a similar case) is more than 1 (one) can not be accepted. Restrictions on the desired PK criminal case the Supreme Court is to provide legal certainty in the process of final settlement of criminal matters. Government through Minister of Law and Human Rights take strategic steps in resolving the legal expediency vision polemic filing legal remedies PK criminal cases, by coordinating state agencies and relevant ministries so as to produce an agreement that filing PK many times can not be executed until the issuance of PP. Therefore still valid set forth in the Judicial Authority Law and the Law on the Supreme Court.Keywords : Legal Aspects, Reconsideration, Criminal Case